Composite photocatalyst, preparation method thereof and hydrogen production method
By combining three-dimensional graphene with two-dimensional MXene, a composite photocatalyst without semiconductors is formed, the problem of insufficient performance of existing photocatalysts is solved, efficient preparation and stability of water decomposition hydrogen is achieved, and the catalytic effect of green and environmental protection is demonstrated. .
Patent Information
- Application Number
- CN202411424120.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-14
AI Technical Summary
The existing photocatalysts have shortcomings in solar light utilization and photon conversion efficiency, resulting in low hydrogen production rate, and the main catalyst is mainly semiconductor materials, with limited performance.
Three-dimensional graphene is used as the main catalyst and two-dimensional MXene to form a composite photocatalyst by mixing under an inert gas and carrying out hydrothermal reaction, and using the light-induced electron emission mechanism to improve the catalytic performance, and a composite catalyst without semiconductor materials is prepared.
High hydrogen production rate and stability are achieved, the hydrogen production rate of decomposed water can reach 1300μmol·h-1·gcat-1, and the efficiency is maintained at more than 70% during recycling, and the catalyst is green and environmentally friendly and has low cost.
Smart Images

Figure CN119303603A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composite photocatalyst and a preparation method thereof and a hydrogen production method. Background Art
[0002] Photocatalytic decomposition of water to produce hydrogen is an important method for converting solar energy into chemical energy. Currently, the most widely used photocatalysts are mainly semiconductor catalysts, such as metal oxides, sulfides, nitrides, and g-C3N4. These catalysts have large band gaps and fast charge recombination rates, resulting in low sunlight utilization and unsatisfactory photon conversion efficiency. In order to increase the hydrogen production rate, those skilled in the art have been looking for methods to improve catalyst performance.
[0003] MXene is a new type of two-dimensional material with excellent conductivity, specific surface area and surface chemical properties, making it an ideal co-catalyst. Combining MXene with graphene is expected to improve the performance of the catalyst.
[0004] CN111744519A discloses a method for preparing a hydrogen evolution catalyst with a three-dimensional MXene-based carrier, using a three-dimensional MXene-based material as a catalyst carrier for hydrogen evolution reaction by electrolysis of water under alkaline conditions, and loading metal particles to prepare a three-dimensional structure catalyst. The method selects graphene or graphene oxide as a carbon material. CN113621989A discloses a method for preparing a nickel-based layered structure electrocatalyst based on MXene / graphene hydrogel electrodeposition, comprising the following steps: mixing MXene, graphene oxide (GO) and a dopant uniformly, and ultrasonically dispersing; loading the dispersion into a hydrothermal kettle and reacting under high temperature conditions to obtain a non-metallic element doped layered MXene / RGO hydrogel; electrodepositing the hydrogel on a metal substrate to obtain a structure-controllable three-dimensional nanostructure electrocatalyst, wherein the catalyst obtained is composed of a MXene / RGO layered material and a three-dimensional layered nickel-based LDH nanosheet array grown on a MXene / RGO substrate. The catalyst obtained by the above method needs to produce hydrogen under electrolysis conditions.
[0005] CN116889867A discloses a method for MXene-derived porous TiO2 / RGO nanosheet composite photocatalyst, which uses MXene as a titanium source, composites with graphene oxide GO, uses TiO2 and GO as self-templates, utilizes their unique thermal conversion characteristics, and calcines at high temperature in a muffle furnace under air atmosphere, forms a strong connection C-Ti between TiO2 and graphene, and obtains a porous and multi-level TiO2 / RGO nanosheet composite photocatalyst. This method uses MXene and graphene to improve the catalytic performance of TiO2, but the main catalyst is still a semiconductor material.
[0006] CN111790417A discloses a method for preparing a MXene-derived TiO2 nanosheet-graphene gel composite material, comprising: forming a graphene oxide aqueous solution in an aqueous solution with graphite oxide; adding MXene to the graphene oxide aqueous solution to obtain a first mixed solution; adding a reducing agent to the first mixed solution to form a MXene-graphene hydrogel under water bath conditions; adding a crystal surface control agent to water to obtain a second mixed solution; placing the MXene-graphene hydrogel in the second mixed solution to perform a hydrothermal reaction to obtain a TiO2 nanosheet-graphene hydrogel; freeze-drying the hydrogel to obtain a TiO2 nanosheet-graphene aerogel composite material. The method uses MXene and graphene to prepare TiO2 nanosheet-graphene, and uses MXene as a raw material for preparing TiO2. The photocatalyst prepared by the method is still mainly semiconductor materials. Summary of the invention
[0007] In view of this, one object of the present invention is to provide a method for preparing a composite photocatalyst, wherein the obtained catalyst has a high hydrogen production rate and stability. Another object of the present invention is to provide a composite photocatalyst obtained by the above method. Another object of the present invention is to provide a method for producing hydrogen by decomposing water.
[0008] The present invention adopts the following technical solutions to achieve the above-mentioned purpose.
[0009] In one aspect, the present invention provides a method for preparing a composite photocatalyst, comprising the following steps:
[0010] 1) Graphene oxide dispersion and Ti3C2T x The dispersions are mixed to obtain a mixture; in the mixture, Ti3C2T x Accounting for graphene oxide and Ti3C2T x 8-25wt% of the total weight;
[0011] 2) subjecting the mixture to a hydrothermal reaction at 100-130° C. for 10-20 hours, then cooling naturally to room temperature, taking out the colloidal cylindrical product containing water, and freeze-drying it to obtain a composite photocatalyst.
[0012] According to the preparation method of the present invention, preferably, in the mixture, Ti3C2T x Accounting for graphene oxide and Ti3C2T x 9 to 15 wt % of the total weight, more preferably 10 to 11 wt %.
[0013] According to the preparation method of the present invention, preferably, the concentration of graphene oxide in the graphene oxide dispersion is 1 to 20 mg / mL; Ti3C2T x Ti3C2T in dispersion xThe concentration is 1-20 mg / mL.
[0014] According to the preparation method of the present invention, preferably, the temperature of the hydrothermal reaction is 110-120° C., and the time is 11-15 hours.
[0015] According to the preparation method of the present invention, preferably, the composite photocatalyst has a diffraction peak of the graphene (002) crystal plane and a diffraction peak of Ti3C2T x (002) diffraction peak of the crystal plane.
[0016] According to the preparation method of the present invention, preferably, the Raman spectrum of the composite photocatalyst has Ti3C2T x The characteristic peaks of and the characteristic peaks of graphene.
[0017] According to the preparation method of the present invention, preferably, the composite photocatalyst has a three-dimensional structure constructed by two-dimensional layers in the SEM photo; and has a Ti3C2T x Image of flakes loaded on the surface of a graphene sheet.
[0018] On the other hand, the present invention also provides a composite photocatalyst prepared by any of the above preparation methods, preferably, the rate of hydrogen production from water decomposition per gram of catalyst is 1350-3000 μmol·h -1 .
[0019] On the other hand, the present invention also provides a method for decomposing water to produce hydrogen. Preferably, under light conditions, the composite photocatalyst is used to decompose water to produce hydrogen; within the first 0.5 hour, the decomposition rate of hydrogen per gram of catalyst is 1350-3000 μmol·h -1 ; After 5 cycles, the hydrogen production rate of the composite photocatalyst remained above 70%.
[0020] The composite photocatalyst of the present invention does not contain semiconductor materials, uses three-dimensional graphene as the main catalyst, and emits high-energy heat / free electrons based on the light-induced electron emission mechanism. The two-dimensional MXene is used as a co-catalyst to enhance the catalytic performance of heat / free electrons, so that the composite photocatalyst of the present invention has a high hydrogen production rate. Under ultraviolet or visible light irradiation, the composite photocatalyst prepared by the present invention can decompose water to produce hydrogen at a rate of up to 1300 μmol·h -1 ·g cat -1 Above, and high stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 XRD pattern of the composite photocatalyst (3DGraphene / MXene-10) prepared in Example 1;
[0022] Figure 2 Raman image of the composite photocatalyst (3DGraphene / MXene-10) prepared in Example 1;
[0023] Figure 3 This is the SEM image of the composite photocatalyst (3DGraphene / MXene-10) prepared in Example 1;
[0024] Figure 4 TEM image of the composite photocatalyst (3DGraphene / MXene-10) prepared in Example 1;
[0025] Figure 5 The performance test results of the composite photocatalysts prepared in the examples and comparative examples for catalytic water decomposition and hydrogen production;
[0026] Figure 6 The test results of the cyclic performance of the composite photocatalyst (3DGraphene / MXene-10) prepared in Example 1 for catalyzing water decomposition to produce hydrogen. DETAILED DESCRIPTION
[0027] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0028] The "hydrogen production rate" mentioned in the present invention refers to the amount of hydrogen produced per gram of catalyst per unit time, with the unit of μmol·h -1 ·g cat -1 , which is used to measure the rate of photocatalytic hydrogen production.
[0029] <Method for preparing composite photocatalyst>
[0030] The present invention has discovered a new enhanced thermal / free electron photocatalytic water decomposition hydrogen production mechanism, and based on this mechanism provides a preparation method of a semiconductor-free composite photocatalyst. The preparation method uses three-dimensional graphene as the main catalyst, based on the light-induced electron emission mechanism, to emit high-energy thermal / free electrons, and uses two-dimensional MXene (Ti3C2T x ,T x =O, OH, F) as a co-catalyst to enhance the catalytic performance of heat / free electrons. Under ultraviolet or visible light irradiation, the prepared composite catalyst can achieve a higher hydrogen production rate when decomposing water to produce hydrogen.
[0031] The preparation method of the composite photocatalyst of the present invention includes a mixing step and a hydrothermal reaction step, which are described in detail below.
[0032] Mixing Steps
[0033] Under the protection of inert gas, graphene oxide dispersion and Ti3C2T x The dispersions are mixed to obtain a mixture.
[0034] The graphene oxide dispersion used in the present invention is similar to Ti3C2T x The dispersion liquid can be directly a commercially available product, or can be prepared by an existing preparation method according to actual needs.
[0035] According to one embodiment of the present invention, graphene oxide can be prepared by a modified Hummer's method. MXene can be prepared by etching the MAX phase with an etchant. The MAX phase is a processable ceramic material known in the art, composed of three elements M, A and X, and its general chemical formula is M (n+1) AX n , where M represents a transition metal element, A represents a main group element, and X represents carbon or nitrogen.
[0036] In the mixture of the present invention, Ti3C2T x Accounting for graphene oxide and Ti3C2T x 8-25wt% of the total weight. In certain technical solutions, in the mixture, Ti3C2T x Accounting for graphene oxide and Ti3C2T x The total weight is 9-15wt%. In other technical solutions, in the mixture, Ti3C2T x Accounting for graphene oxide and Ti3C2T x The total weight is 10-11 wt%. The present invention finds that graphene oxide and Ti3C2T x By controlling the mass fraction of within the above range, both the main catalyst and the co-catalyst can function more stably, thereby ensuring the efficient hydrogen production rate and stability of the composite photocatalyst.
[0037] According to one embodiment of the present invention, the concentration of graphene oxide in the graphene oxide dispersion may be 1 to 20 mg / mL, preferably 2 to 15 mg / mL, and more preferably 5 to 10 mg / mL. x Ti3C2T in dispersion x The concentration of may be 1 to 20 mg / mL, preferably 2 to 15 mg / mL, and more preferably 5 to 10 mg / mL.
[0038] According to a specific embodiment of the present invention, Ti3C2T x The chemical formula is:
[0039] Ti3C2T x ,T x =O, OH and F.
[0040] In the present invention, the inert gas is selected from at least one of helium (He), neon (Ne), and argon (Ar); preferably, the inert gas is selected from at least one of helium (He) and argon (Ar). The inert gas prevents MXene from being oxidized and also prevents the oxidized MXene from further reacting with graphene oxide under oxygen-containing conditions, thus providing a guarantee for the stable progress of the next hydrothermal reaction.
[0041] In order to obtain a better reaction effect, the mixture may be stirred. The stirring time may be 5 to 30 minutes, preferably 10 to 25 minutes, and more preferably 15 to 20 minutes. Reasonable stirring time can ensure that MXene and graphene oxide are mixed more evenly, which is beneficial to the next step of heating reaction and ensures the three-dimensional structure of three-dimensional graphene and two-dimensional MXene.
[0042] Hydrothermal reaction steps
[0043] Graphene oxide dispersion and Ti3C2T x The mixture of the dispersion liquid undergoes a hydrothermal reaction and then cools naturally to room temperature. The colloidal cylindrical product containing water is taken out and freeze-dried to obtain a composite photocatalyst.
[0044] According to one embodiment of the present invention, the hydrothermal reaction can be carried out in a high-pressure reactor, and the pressure in the high-pressure reactor is 0.1-3 MPa during the reaction.
[0045] In the present invention, preferably, the temperature of the hydrothermal reaction can be 100-130°C, preferably 110-120°C, and more preferably 115-120°C. The hydrothermal reaction time can be 10-20h, preferably 11-15h; more preferably 12-13h. Reasonable hydrothermal temperature and hydrothermal time can realize the reduction of graphene oxide to graphene, and at the same time are conducive to the formation of a three-dimensional / two-dimensional structure of a three-dimensional graphene / Mxene photocatalyst, ensuring that the two-dimensional Mxene is stably loaded on the three-dimensional graphene, and is conducive to improving the stability of the catalyst.
[0046] According to one embodiment of the present invention, freeze drying is preferably vacuum freeze drying. Vacuum freeze drying can be performed using a vacuum freeze dryer, which is selected from a gland freeze dryer, a multi-manifold freeze dryer, a bell freeze dryer, an in-situ freeze dryer, a rotary dynamic freeze dryer, and a vibration dynamic freeze dryer, preferably a bell freeze dryer, an in-situ freeze dryer, and a rotary dynamic freeze dryer.
[0047] According to another embodiment of the present invention, the freeze-drying conditions of the present invention are as follows:
[0048] The cold trap temperature may be -80 to -10°C, preferably -75 to -20°C, more preferably -70 to -45°C;
[0049] The vacuum degree may be 0.1 to 50 Pa, preferably 1 to 30 Pa, more preferably 5 to 20 Pa;
[0050] The drying time may be 10 to 300 hours, preferably 50 to 250 hours, and more preferably 80 to 150 hours.
[0051] In addition to eliminating moisture, freeze-drying is more conducive to the formation of three-dimensional graphene and two-dimensional MXene structures and maintaining a stable state; at the same time, freeze-drying can prevent graphene from being oxidized and degraded, which is beneficial to maintaining the original performance of MXene.
[0052] According to one embodiment of the present invention, the composite photocatalyst prepared by the preparation method of the present invention has a diffraction peak of the graphene (002) crystal plane and a diffraction peak of Ti3C2T x The diffraction peak of the (002) crystal plane. The Raman spectrum of the composite photocatalyst has Ti3C2T x The SEM photo of the composite photocatalyst has a three-dimensional structure constructed by two-dimensional sheets; the TEM photo has Ti3C2T x In the composite photocatalyst with the above characteristics, the two-dimensional MXene is loaded on the three-dimensional graphene to form a stable three-dimensional structure, which is beneficial to improve the catalytic hydrogen production rate and stability.
[0053] <Composite photocatalyst>
[0054] The composite photocatalyst of the present invention can be obtained by adopting the above method.
[0055] In the composite photocatalyst of the present invention, two-dimensional MXene is stably loaded on three-dimensional graphene. Two-dimensional MXene has excellent electrical conductivity, specific surface area and surface chemical properties. The high electrical conductivity of two-dimensional MXene as a co-catalyst is conducive to the rapid transfer of hot electrons generated by three-dimensional graphene; the excellent surface chemical properties, especially hydrophilicity, are conducive to the enrichment of water molecules, thereby promoting the decomposition of water, enhancing the catalytic performance of the main catalyst three-dimensional graphene, and significantly enhancing the hydrogen production rate. At the same time, the composite photocatalyst of the present invention does not contain semiconductor materials, is green and environmentally friendly, and has low cost.
[0056] <Method of Decomposing Water to Produce Hydrogen>
[0057] The present invention also provides a method for decomposing water to produce hydrogen, wherein the composite photocatalyst described above is used to decompose water to produce hydrogen under illumination conditions. The specific illumination conditions are as follows: the spectrum range of the xenon lamp is 200 to 1000 nm. The light power incident on the reaction liquid surface can be 50 to 500 mW, preferably 100 to 350 mW, and more preferably 150 to 300 mW;
[0058] In the first 0.5 hours, the rate of hydrogen production from water decomposition per gram of catalyst is 1350-3000 μmol·h -1 , showing very excellent hydrogen production performance; after 5 cycles, the hydrogen production rate of the composite photocatalyst remained above 70%, with good cycle stability.
[0059] <Test method>
[0060] The test was carried out using an online photocatalytic reaction system equipped with a gas chromatograph according to standard procedures.
[0061] <Raw material preparation>
[0062] The raw materials used in the following examples and comparative examples are described below:
[0063] Ti3C2T x Dispersion, concentration: 8.6 mg / mL; prepared by etching Ti3AlC2 phase with LiF / HCl.
[0064] Graphene oxide dispersion, concentration: 6.57 mg / mL; prepared by improved Hummer's method.
[0065] Examples 1 to 3 and Comparative Examples 1 to 3
[0066] A dispersion containing 70 mg of graphene oxide and Ti3C2T x The dispersions were mixed to a total volume of 70 mL and stirred for 10 min under argon protection to obtain a mixture.
[0067] The mixture was transferred into a 100 mL polytetrafluoroethylene-lined autoclave, heated to 120°C, and subjected to hydrothermal reaction for 12 hours. The mixture was naturally cooled to room temperature, and then the colloidal cylindrical product containing water was taken out of the autoclave. The colloidal cylindrical product was freeze-dried to obtain a composite photocatalyst. Freeze drying was performed using a freeze dryer, cold trap temperature: -60°C, vacuum degree: 10Pa, and drying time: 100 hours. The detailed parameters and properties of the obtained composite photocatalyst are shown in Table 1.
[0068] In Comparative Example 1, Example 1, Example 2 and Example 3, the Ti3C2T x Accounting for graphene oxide and Ti3C2Tx Composite photocatalysts were prepared by mixing 5%, 10%, 15% and 20% of the total weight, and the corresponding composite photocatalysts were represented as 3DGraphene / MXene-5, 3DGraphene / MXene-10, 3DGraphene / MXene-15 and 3DGraphene / MXene-20, respectively.
[0069] Table 1
[0070]
[0071] It can be seen from Table 1 that Ti3C2T x Only when the weight is controlled within an appropriate range can a higher hydrogen production rate be obtained.
[0072] The phase and crystal structure of the composite photocatalyst (3D Graphene / MXene-10) prepared in Example 1 were characterized and analyzed by X-ray diffraction (XRD). Figure 1 As shown in the XRD spectrum, the graphene (002) crystal plane and Ti3C2T x (002) crystal plane diffraction peaks can all be observed.
[0073] The Raman spectrum of 3DGraphene / MXene-10 is as follows Figure 2 As shown, Ti3C2T x The characteristic peaks of graphene and the D peak and G peak of graphene were all observed.
[0074] The SEM characterization results of 3DGraphene / MXene-10 are as follows Figure 3 As shown in Figure 2, a three-dimensional structure constructed by two-dimensional sheets was observed. In the TEM results of 3DGraphene / MXene-10 ( Figure 4 ), it was observed that Ti3C2T x The flakes are supported on the surface of the graphene sheet (marked by a white dashed circle).
[0075] The composite photocatalysts prepared in Examples 1 to 3 and Comparative Example 3 were tested for their performance in catalytic decomposition of water to produce hydrogen under illumination. The xenon lamp spectrum range was 200 to 1000 nm, and the light power incident on the reaction liquid surface was 260 mW. Using the same preparation method as in Example 1, three-dimensional graphene (3D Graphene) without MXene and pure MXene (Con-MXene) without graphene were prepared as Comparative Examples 1 and 2. The test results are shown in Figure 2. Figure 5As shown, Con-MXene generates almost no hydrogen, indicating that pure MXene has no photocatalytic activity. 3DGraphene exhibits photocatalytic activity under light, further confirming the catalytic ability of three-dimensional graphene to generate heat / free electrons. The composite photocatalysts prepared in Examples 1 to 3 significantly increase the hydrogen production rate when catalyzing the decomposition of water to produce hydrogen.
[0076] The hydrogen production rate in the first 0.5 hours of catalytic decomposition of water to produce hydrogen under light was detected. The composite photocatalysts prepared in Examples 1 to 3 showed a hydrogen production rate of 1300 μmol·h -1 ·g cat -1 The above hydrogen production rate is significantly higher than that of comparative example 1 (3D Graphene, 392 μmol·h -1 ·g cat -1 ), and is significantly higher than Comparative Example 3.
[0077] The photocatalytic cyclic stability of the composite photocatalyst (3D Graphene / MXene-10) prepared in Example 1 was tested for a total of 5 cycles, with each cycle test lasting 4 hours of hydrogen production. The test results are shown in Figure 2. Figure 6 As shown, with the increase of the number of cycles, the amount of hydrogen produced slightly decays, and after 5 cycles, the hydrogen production rate remains at 71%, indicating that the composite photocatalyst of the present invention has good cycle stability.
[0078] Comparative Examples 4-5
[0079] The hydrothermal reaction temperature was changed, and the other conditions were the same as those in Example 1 to obtain a composite photocatalyst. For detailed parameters and properties, see Table 2.
[0080] Table 2
[0081]
[0082] It can be seen from Table 2 that a lower hydrothermal reaction temperature is not conducive to obtaining a composite photocatalyst with a stable three-dimensional / two-dimensional structure, and reduces the hydrolysis hydrogen production rate of the composite photocatalyst.
[0083] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.
Claims
1. A method for preparing a composite photocatalyst, comprising the following steps: 1) Under the protection of inert gas, graphene oxide dispersion and Ti3C2T x The dispersions are mixed to obtain a mixture; in the mixture, Ti3C2T x Accounting for graphene oxide and Ti3C2T x 8-25wt% of the total weight; 2) subjecting the mixture to a hydrothermal reaction at 100-130° C. for 10-20 hours, then cooling naturally to room temperature, taking out the colloidal cylindrical product containing water, and freeze-drying it to obtain a composite photocatalyst.
2. The preparation method according to claim 1, characterized in that: In the mixture, Ti3C2T x Accounting for graphene oxide and Ti3C2T x 9-15wt% of the total weight.
3. The preparation method according to claim 2, characterized in that: In the mixture, Ti3C2T x Accounting for graphene oxide and Ti3C2T x 10-11 wt% of the total weight.
4. The preparation method according to claim 1, characterized in that: The concentration of graphene oxide in the graphene oxide dispersion is 1-20 mg / mL; Ti3C2T x Ti3C2T in dispersion x The concentration is 1-20 mg / mL.
5. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 110-120°C and the time is 11-15 hours.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The XRD spectrum of the composite photocatalyst has the diffraction peak of graphene (002) crystal plane and the diffraction peak of Ti3C2T x (002) diffraction peak of the crystal plane.
7. The preparation method according to any one of claims 1 to 5, characterized in that: The Raman spectrum of the composite photocatalyst has Ti3C2T x The characteristic peaks of and the characteristic peaks of graphene.
8. The preparation method according to any one of claims 1 to 5, characterized in that: The SEM image of the composite photocatalyst shows a three-dimensional structure constructed by two-dimensional layers; the TEM image shows Ti3C2T x Image of flakes loaded on the surface of a graphene sheet.
9. A composite photocatalyst prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The rate of hydrogen production from water decomposition per gram of catalyst is 1350-3000 μmol·h -1 .
10. A method for producing hydrogen by decomposing water, characterized in that: Under light conditions, the composite photocatalyst of claim 9 is used to decompose water to produce hydrogen; within the first 0.5 hour, the rate of hydrogen production from water decomposition per gram of catalyst is 1350-3000 μmol·h -1 ; After 5 cycles, the hydrogen production rate of the composite photocatalyst remained above 70%.
Citation Information
Patent Citations
Photocatalyst for photocatalytic water splitting as well as preparation method and application thereof
CN110180577A
Photocatalytic hydrogen production promoter, photocatalytic system and hydrogen production method
CN113441144A
Graphene quantum dot / MXene nanosheet two-dimensional composite material as well as preparation method and application thereof
CN113718281A
Ultralight porous aerogel based on MXene-graphene compounding, preparation method and application
CN115939423A